2023
DOI: 10.1002/wene.474
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for design and optimization of organic Rankine cycle plants: A review of current status and future perspectives

Abstract: The organic Rankine cycle (ORC) is widely acknowledged as a sustainable power cycle. However, the traditional approach commonly adopted for its optimal design involves sequential consideration of working fluid selection, plant configuration, and component types, before the optimization of state parameters. This way, the design process fails to achieve an optimal design in most cases, since the process relies heavily on empirical judgments. To improve the design process, researchers have been exploring lately t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In general, within ML, a distinctive requirement involves training with a distinct dataset. It is necessary to thoroughly examine input variables across various stages of both the training and testing processes [165]. The objective is to assess the potential impact of the TC and NC variables on enhancing stock-price prediction.…”
Section: Comparing the Impact Of T And T+ Variablesmentioning
confidence: 99%
“…In general, within ML, a distinctive requirement involves training with a distinct dataset. It is necessary to thoroughly examine input variables across various stages of both the training and testing processes [165]. The objective is to assess the potential impact of the TC and NC variables on enhancing stock-price prediction.…”
Section: Comparing the Impact Of T And T+ Variablesmentioning
confidence: 99%
“…Moreover, a recent review article [79] described and reported an overview of artificial intelligence in ORC design. Another review article [80] described the overview of ML for design and optimization of ORC including its classification These review articles are useful resources for summarizing the state of knowledge in this area and developing more integrated advanced control systems. Moreover, in our opinion, an intriguing topic that requires more research in the future is the identification of appropriate control systems that are specifically adapted to particular components.…”
Section: Mpcmentioning
confidence: 99%